Environmental Security in the Arctic Region : The Nordic Countries' Role - Terekhov, Viktor (2015)
The Arctic environment is changing endangering security both within and beyond the Arctic region. Taking into account the Nordic countries’ involvement in Arctic affairs, the project includes a study on Nordic environmental activities in the region. For this purpose, the methodology is based on applying comparative analysis to the Nordic countries’ Arctic environmental activities. The sources used in the study include the Nordic countries’ Arctic strategies, chairmanship and cooperation programmes in the Arctic Council, the Barents Euro-Arctic Council and the Nordic Council of Ministers as well as reports and assessments and other relevant documents. According to the results, the Nordic countries’ positions and activities on Arctic environmental issues agree mainly due to their environmental thinking, their connection with the Arctic region and solidarity on Arctic issues that can be achieved through the Nordic Council of Ministers. The Nordic countries comply with three prerequisites required to achieve environmental security in the Arctic region, which are climate change mitigation and adaptation, pollution prevention and sustainable exploitation of natural resources, namely marine bioresources. Furthermore, the Nordic countries contribute to comprehensive security in the region, since mitigation activities related to Arctic climate change are necessary to underpin the stability in societal, economic, political and military sectors of security. On the other hand, the Nordic countries’ activities do not contribute to achieving a successful securitization of environmental threats in the Arctic, which means that the current environmental situation in the region is relatively stable, and therefore, there is time to take proper measures in order to prevent greater Arctic environmental problems and securitization thereof in the future.